Pengaruh Resistensi Kepemimpinan Terhadap Perilaku Pegawai Dikantor Sekretariat Daerah Kota Gunungsitoli - Niat Murni Waruwu; Eliagus Telaumbanua; Meiman H. Waruwu; Emanuel Zebua (Lembaga Pengembangan Kinerja Dosen, 2025)
Organizational change is an inevitable necessity to achieve goals more effectively and efficiently. However, in practice, change often leads to resistance, especially when it involves leadership and structural positions. This study aims to analyze leadership resistance toward employee behavior at the Regional Secretariat Office of Gunungsitoli City, focusing on the leadership policy that demoted certain leaders to regular staff positions. This phenomenon reveals rejection of the newly implemented management system, which affects employee behavior, motivation, and performance. The study employs a qualitative approach with descriptive-analytical methods, collecting data through observations, in-depth interviews, and document analysis. The findings indicate that leadership resistance is influenced by a lack of effective communication, minimal employee involvement in the change process, and concerns about personal impact. These findings highlight the importance of participatory and communicative change management strategies to address resistance, ensuring the continuity of innovation and improvement of organizational performance. This research contributes theoretically to the development of change management in the public sector and offers practical insights for policymakers in creating a work environment that is adaptive to organizational dynamics.